A METHODOLOGY FOR REDUCING ENERGY UTILIZATION IN DENSE WIRELESS SENSOR NETWORKS - Kumar, Senthil; Prabhu, Boselin; Rajkumar; Sophia, S. (International Journal of Research -GRANTHAALAYAH, 2016)
The development of wireless sensor networks was motivated by military applications such as battlefield surveillance; today such networks are used in many industrial and consumer applications, such as industrial process monitoring and control, machine health monitoring, and so on. Wireless sensor Networks (WSNs), is one of the most rapidly growing scientific domain. This is because of the development of advanced sensor nodes with extremely low cost and the potential application of such sensor nodes are ever growing. One of the characteristic feature of WSNs compared to the traditional wireless communication networks, is the power awareness, due to the fact that the batteries of the sensor nodes have restricted lifetime and are difficult to be replaced. This is why we focus on power awareness, while the traditional wireless networks mainly focuses on the QOS. A typical sensor node consumes most of its energy during communication. However, energy expenditure takes place while performing sensing and data processing too. This work suggests the development of an advanced hierarchical routing technique, which gives improved performance over the existing techniques. Power consumption is highly reduced, thereby greatly reducing the cost of network and hence the lifetime of nodes can be greatly improved.